Primary care pedometer-based walking intervention: mixed-methods results from 3 year follow-up of PACE-UP cluster-randomised controlled trial. (November 2017) - Wahlich, Charlotte; Cook, Derek; Kerry, Sally; Limb, Elizabeth; Victor, Christina; Iliffe, Steve; Ussher, Michael; Whincup, Peter; Ekelund, Ulf; Fox-Rushby, Julia; Furness, Cheryl; Beighton, Carole; et al.
Abstract: Background: Maintenance of physical activity is important for health, but few trials provide long-term objective data or qualitative evaluation of factors affecting this maintenance. The PACE-UP three-arm (postal, nurse-support, control) primary care cluster-randomised controlled trial recruited 1023 adults aged 45–75 years into a 12 week pedometer-based intervention including a physical activity diary and handbook incorporating behaviour change techniques; controls received usual care. Recruitment was from Sept 1, 2012, to Oct 31, 2013. At 12 months, step-counts increased by around a tenth, and time in moderate-to-vigorous physical activity (MVPA) in bouts by around a third in postal and nurse-supported arms compared with control. Using a mixed-methods approach at 3 year follow-up of the PACE-UP cohort, we aimed to assess whether the intervention effects persisted. Methods: Assessments were done between Oct 1, 2015, and Nov 30, 2016. Mean daily step-counts and total weekly minutes of MVPA in bouts of 10 min or more at 3 years were collected with 7 day GT3X+ accelerometry (Actigraph, Pensacola, FL, USA) for all trial arms. Outcomes were regressed on baseline values to estimate change in treatment groups compared with control. Sensitivity analysis assessed missing data effects. Semi-structured telephone interviews were conducted with 60 participants. Interviews were audio recorded, transcribed, and coded, and thematic analysis was performed. Ethics approval was given by the National Research Ethics Service Committee London (Hampstead). Findings: 3 year follow-up with accelerometry was 67% (681/1023). Compared with controls, intervention groups maintained higher steps per day (postal 627 additional steps[95% CI 198–1056], p=0·004; nurse 670 [237–1102], p=0·002), and more total weekly minutes of MVPA in bouts (postal 28 [7–49], p=0·009; nurse 24 [3–45], p=0·03). Results were robust to sensitivity analyses. Most interviewees felt that PACE-UP had increased their awareness of their physical activity. Facilitators to physical activity maintenance included self-motivation, social-support, and maintaining good health, with poor health and lack of time as barriers. Interpretation: At 3 year follow-up of PACE-UP, step-counts and bouts of MVPA persisted, with no difference between intervention groups, suggesting that a primary care pedometer intervention, delivered by post or with nurse support, could help address the public health physical inactivity challenge. Major future challenges are how to apply this kind of effective intervention widely in the population and how to transform perceived barriers into facilitators (eg, poor physical health). Funding: National Institute for Health Research Health Technology Assessment Programme (project number HTA 10/32/02).